Recessive Charcot-Marie-Tooth and multiple sclerosis associated with a variant in MCM3AP. Issue 1 (3rd September 2019) - Sedghi, Maryam; Moslemi, Ali-Reza; Cabrera-Serrano, Macarena; Ansari, Behnaz; Ghasemi, Majid; Baktashian, Mojtaba; Fattahpour, Ali; Tajsharghi, Homa
Abstract: Variants in MCM3AP, encoding the germinal-centre associated nuclear protein, have been associated with progressive polyneuropathy with or without intellectual disability and ptosis in some cases, and with a complex phenotype with immunodeficiency, skin changes and myelodysplasia. MCM3AP encoded protein functions as an acetyltransferase that acetylates the replication protein, MCM3, and plays a key role in the regulation of DNA replication. In this study, we report a novel variant in MCM3AP (p.Ile954Thr), in a family including three affected individuals with characteristic features of Charcot-Marie-Tooth neuropathy and multiple sclerosis, an inflammatory condition of the central nervous system without known genetic cause. The affected individuals were homozygous for a missense MCM3AP variant, located at the Sac3 domain, which was predicted to affect conserved amino acid likely important for the function of the germinal-centre associated nuclear protein. Our data support further expansion of the clinical spectrum linked to MCM3AP variant and highlight that MCM3AP should be considered in patients with accompaniment of recessive motor axonal Charcot-Marie-Tooth neuropathy and multiple sclerosis. Abstract : Segregation of MCM3AP variants has previously been reported in patients with progressive polyneuropathy with or without intellectual disability. Sedghi et al. report the co-segregation of MCM3AP variant with recessive Charcot-Marie-Tooth and development multiple sclerosis in three affected individuals of a family, further expanding the clinical spectrum linked to MCM3AP variant. Graphical Abstract: